Caipira, brabo e matuto: xenofobias aos migrantes sertanejo-amazônicos em A selva (1930), de Ferreira de Castro - CORREA, Maria Fernanda Teixeira (2024)
In literature, it is possible to see two geographically distinct scenarios intertwining: the arid sertão region and the jungle. In the novel A Selva/The Jungle (1930) by Ferreira de Castro, the sertanejos, people from the arid sertão region of the Brazilian northeast, embark on an obstinate search for better living conditions, exploring the natural rubber farms and the Amazon rainforest, although, along the way, they encounter several challenges, including exploration, dehumanization and social prejudice. Therefore, in this work, we aim to reflect on the manifestations of xenophobia suffered by the sertanejos, in addition to the process of construction of internalized xenophobia. We use analytical bibliographic research, in which we will map and analyze such terms and situations that highlight xenophobia in this process. In this scenario, we will benefit from the studies of Erving Goffman (2004), in which he argues about stigma and the creation of stereotypes that influence the social identity of a given person or social group, Gancho (2006) regarding the elements of the narrative, among others that contributed to research in general. As a result, the present work presents a vast representation of the manifestations of xenophobia practiced against the sertanejos in the studied novel.